Evaluation of three saponification methods on two types of fat as protection against bovine ruminal degradation. - Proaño, F.; Stuart, J. R.; Flores, L.; Herrera, Magaly; Medina, Yolaine; Sarduy, Lucía (Cuban Journal of Agricultural Science, 2016)
To evaluate the saponification of two fat raw matters, ovine suet and residual of African palm oil (Elaeis guineensis), by means of the use of sodium hydroxide, potassium and calcium, with the purpose of protecting these fats from the bovine ruminal degradation, an experiment according to a completely random design, with factorial arrangement 3 x 2 was conducted. A bromatological analysis of the obtained soaps, evaluation of consistency and profitability by means of cost-benefit indicator was carried out. The variance analysis showed significant interaction among the studied factors. The dry matter was higher in the residual of palm oil soaps treated with calcium, sodium and potassium (P ≤ 0001). Likewise, ash was higher in these soaps (P ≤ 0001).It was higher with the potassium hydroxide. This hydroxide allowed soaps with higher (P < 0, 0002) protein concentrations (with both fat sources).The higher concentration of fat was in the ovine suet soaps (P ≤ 0001).The calcium hydroxide saponification acted in an optimum way in the consistency of residual palm oil and ovine suet soaps. The cost – benefit showed higher values (1.25) in the residual palm oil soaps protected with calcium. It is concluded that the studied saponification methods (sodium, potassium and calcium hydroxide) allowed an appropriate nutrients concentration in the obtained soaps, high contribution of fat in ovine suet, adequately hardness in calcium soaps, acceptable levels of in vitro solubility and high profitability for calcium soaps.Key words: protection, fat sources, ruminant